Independent Farmer Card Program in the Perspective of Effectiveness Theory in Bojonegoro Regency - Rupiarsieh, Rupiarsieh; Wulandari, Septi; Wahyunita, Evi; Septiana, Vita Nugrah (Publik : (Jurnal Ilmu Administrasi), 2025)
This study examines the effectiveness of the Independent Farmer Card Program (Kartu Petani Mandiri/KPM) implemented by the Food Security and Agriculture Office of Bojonegoro Regency as a policy innovation to address structural problems in the agricultural sector. Farmers in the region still face obstacles such as limited access to capital, technology, and market information, which hinder productivity and welfare. The KPM program was introduced to facilitate access to farming inputs, capital assistance, training, and support services. However, various implementation challenges remain, including delayed distribution of aid, limited human resource capacity, and uneven program outreach. Employing a qualitative descriptive method, data were collected through interviews, observations, and documentation to assess program effectiveness based on five key indicators: program understanding, target accuracy, timeliness, goal achievement, and real change. The findings indicate that while the KPM program has been effective in improving agricultural productivity and providing direct benefits such as fertilizer access and scholarships for farmers' children, its impact is not yet evenly distributed due to socialization and administrative barriers. Strengthening coordination among stakeholders, improving data accuracy, and enhancing the capacity of implementing actors are crucial for the program’s sustainability and equity. This research provides practical insights into the implementation of targeted agricultural assistance in a decentralized governance context.